Public response to a proposed field trial of genetically engineered mosquitoes in the United States - Bloss, Cinnamon (Henry Stewart Talks, 2018)
Recent transmissions of mosquito-borne disease, Oxitec proposal of a Florida Keys trial of genetically engineered mosquitoes, FDA “Finding of No Significant Impact”, FDA public comments analyzed, Themes: ecological implications; human health; concerns about genetically modified organisms generally; government and industry mistrust, Georeferenced attitudes to genetically engineered mosquitoes, Results of Florida’s non-binding referendum, Importance of public trust to successful public health interventions